Preservation of Antibodies to Vaccine-Controlled Infections in Children WITH Oncological Diseases - S. M. Kharit; Yu. E. Konstantinova; O. V. Goleva; A. A. Ruleva; K. K. Tikhomirova; O. V. Iozefovich; I. V. Fridman (Эпидемиология и вакцинопрофилактика)
Relevance. Cancer therapy forms a temporary immunosuppressive state, which determines an increase in the frequency and severity of infectious diseases. Vaccination is a highly effective and safe way to protect against infection, but people with immunodeficiency have risks of inefficiency and complications. To substantiate the need for immunoprophylaxis in cancer patients after therapy, it is important to understand the preservation of their specific response after previous vaccinations.The aim of the study was to assess the safety of antibodies to vaccine–controlled infections in children with oncological diseases after therapyMaterials and methods. The safety of antibodies to vaccine-controlled infections was studied in 3 groups: 1 -in patients with oncological (n=62); 2-in the group (n=43) withoutoncological diseases, but who received immunosuppressive (IST) and/or polychemotherapy (PCT) and/or hematopoietic stem cell transplantation (HSCT), and 3– in healthy children (n=31 – comparison group). The concentration of antibodies was determined by the ELISA method. The minimum protective level was considered to be the amount for measles ³0.18 IU/ml, rubella - ³25 IU/ml; hepatitis B - ³10 IU/ml; diphtheria – 0.03 IU/ml and higher. The coefficient of positivity, estimated as protective against mumps, was ³1.0.Results. It was found that from 41.7% to 93.7% of children with cancer lose post-vaccination immunity to the studied vaccine antigens. The number of children who retained the protective level of antibodies in groups 1 and 2 was significantly less than in the comparison group. There were no significant differences in the level of those protected from diphtheria and rubella. The maximum effect on the loss of antibodies is provided by the performed HSCT. For diphtheria and rubella antibodies, the differences are not pronounced. The possible connection of genetic breakdowns in 35 examined children with oncological diseases and the safety of antibodies was analyzed. It turned out that in the presence of chromosomal deletions, antibodies to measles were lost in 100% of cases and to diphtheria in 75%, which was different from other chromosomal abnormalities.Conclusion. The safety of antibodies in patients with a history of cancer is influenced by the presence of HSCT in therapy, the type of genetic breakdown, as well as the peculiarity of the vaccine antigen. Children with oncological diseases, as well as with non-oncological ones, but who have received HSCT therapy, should be vaccinated again against vaccine-controlled infections, despite the indication of the presence of vaccinations before therapy.